Exploring underlying drivers and factors, and the impact of social networks on farmers' use of integrated pest management strategies in Bangladesh - Aravindakshan, Sreejith; Abdur Rashid; Syed Nurul Alam; Mohammad Shamsul Hoq; Morsalina Khatun; Moniruzzaman, M.; Hasan, M.K.; Md. Harun-Or-Rashid; Krupnik, Timothy J. (TAFSSA, 2024)
This report presents findings from a research study conducted under the Bangladesh Integrated Pest Management Activity (IPMA) involving 2,250 respondents, including 2,000 farmers, 100 dealers/retailers, 100 local service providers (LSPs) or pesticide sprayers, and 50 Sub-Assistant Agriculture Officers (SAAOs) across ten districts in Bangladesh. The study examined pest management strategies among farmers, both IPM users and non-users, focusing on decision-making processes, factors influencing IPM usage in five key crops—rice, maize, tomato, mungbean, and mango—and the role of stakeholders and social networks in pesticide selection and use.